2002
DOI: 10.1080/09687680110110048
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the structure and function of the 5-HT 3 receptor: a model ligand-gated ion channel (Review)

Abstract: The ligand-gated ion channel superfamily of neurotransmitter receptors are proteins responsible for rapid transmission of nerve impulses at the synapse and have, therefore, been the subject of intensive research for many years. The cys-loop family, of which the 5-HT3 receptor is a member, includes the nicotinic acetylcholine receptor, the GABAA receptor and the glycine receptor. A diverse range of endogenous and artificial ligands activate these receptors, but, nevertheless, the family shares many similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
146
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 149 publications
3
146
0
2
Order By: Relevance
“…5); thus, it is not surprising that changing it to serine or alanine in the 5-HT 3 native aromatic, phenylalanine, resulted in changed functional receptor characteristics (an ϳ10-fold increase in EC 50 ) but not in binding affinity (K d not significantly different from WT), thus supporting a role for the hydroxyl group in receptor gating. Extensive site-directed mutagenesis of the residue at this location has shown that it is important in the nACh receptor (39), the ␥-aminobutyric acid A receptor (40), and the glycine receptor (41), although there is some debate as to whether it affects the binding affinity (42) or the gating constant (43).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5); thus, it is not surprising that changing it to serine or alanine in the 5-HT 3 native aromatic, phenylalanine, resulted in changed functional receptor characteristics (an ϳ10-fold increase in EC 50 ) but not in binding affinity (K d not significantly different from WT), thus supporting a role for the hydroxyl group in receptor gating. Extensive site-directed mutagenesis of the residue at this location has shown that it is important in the nACh receptor (39), the ␥-aminobutyric acid A receptor (40), and the glycine receptor (41), although there is some debate as to whether it affects the binding affinity (42) or the gating constant (43).…”
Section: Discussionmentioning
confidence: 98%
“…Among the different family members, the 5-HT 3 1 receptor has the closest functional homology with the nicotinic acetylcholine (nACh) receptor. The nACh receptor is particularly well characterized, because although no high resolution x-ray crystal structure is known, a vast array of techniques including chemical modification, sitedirected mutagenesis, electron microscopy, and molecular modeling have provided a reasonable understanding of the structure-function relationships of the receptor.…”
mentioning
confidence: 99%
“…The 5-hydroxytryptamine (serotonin) type 3 (5-HT 3 ), nicotinic acetylcholine (nACh), γ-aminobutyric acid type A (GABA A ), and glycine receptors belong to the Cys-loop ligand-gated ion channel superfamily, which mediate synaptic transmission and modulate neurotransmitter release (Ortells & Lunt, 1995;Reeves & Lummis, 2002). Members of the superfamily are pentamers formed by assembly of one (homomeric) or different (heteromeric) subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin 5-HT 3 receptors (5-HT 3 R) are members of the Cys loop receptor superfamily of ligand-gated ion channels (Reeves and Lummis, 2002) that includes the GABA A , glycine, and nicotinic acetylcholine receptors (AChR). 5-HT 3 R antagonists are used clinically for the prevention and amelioration of nausea and emesis (Costall and Naylor, 2004).…”
Section: Introductionmentioning
confidence: 99%